Effects of Early-Life Exposure to Sanitation on Childhood Cognitive Skills : Evidence from India's Total Sanitation Campaign - Spears, Dean; Lamba, Sneha (World Bank, Washington, DC, 2014)
Early life health and net nutrition shape childhood and adult cognitive skills and human capital. In poor countries -- and especially in South Asia -- widespread open defecation without making use of a toilet or latrine is an important source of childhood disease. This paper studies the effects on childhood cognitive achievement of early life exposure to India's Total Sanitation Campaign, a large government program that encouraged local governments to build and promote use of inexpensive pit latrines. In the early years of the program studied here, the TSC caused six-year-olds exposed to it in their first year of life to be more likely to recognize letters and simple numbers. The results suggest both that open defecation is an important threat to the human capital of the Indian labor force, and that a program feasible to low capacity governments in developing countries could improve average cognitive skills.